The role of CACNβ4 in zebrafish development - Harrell, Cory Jean, author; Garrity, Deborah M., advisor; Mykles, Donald L., committee member; DeLuca, Jennifer G., committee member (Colorado State University. Libraries, 2010)
The calcium channel β4 subunit (CACNβ4) is an intracellular auxiliary protein of voltage-gated calcium channels. It is a member of the membrane-associated guanylate kinase (MAGUK) family of proteins. Mutations in the CACNβ4 subunit are associated with ataxia and seizures in mice and with epilepsy in humans. Since known mutant alleles of CACNβ4 are not embryonic lethal in mammals, the developmental functions of the protein are unclear. The best characterized role for the β4 subunit is to facilitate the translocation of the calcium channel α subunit to the plasma membrane and the modulation of the channel gating. Recently, additional roles have been proposed for the β subunits including facilitation of vesicle docking, attenuation of gene silencing and transcriptional regulation of calcium channel turnover. In studying the functional roles of the CACNβ4 gene, we unexpectedly discovered that targeted knockdown of CACNβ4 genes in zebrafish led to arrest or delay of epiboly and the subsequent death of the early embryo. Embryonic death can be rescued by co-injection with full-length RNA of human CACNβ4 (homologue). In this study we investigated the sub-cellular localization and critical domains of the β4 proteins. Upon injection of a construct with GFP-tagged β4 gene under the control of the β-actin promoter we observed that the β4 protein is present in the nucleus in higher concentrations than in the rest of the cell. We determined via rescue experiments with truncated RNA constructs that the N-terminus and the chromoshadow binding element (CBE) are necessary for CACNβ4's function during gastrulation. Our findings suggest that CACNβ4 has a nuclear role, potentially interacting with chromobox family proteins, which is necessary for early zebrafish development.
Keywords: zebrafish; transgenic; epiboly; embryo; development; CACNβ4; Calcium channels; Zebra danio -- Development